Criminal recidivism in Islamic criminal jurisprudence, its causes and effects -A comparative study with civil law- - Al-Tamimi, Emad (Jordan Journal of Islamic Studies, 2023)
The crime of recidivism is a heavy burden that confronts crime specialists. Despite the efforts made in this field, which are represented in seminars, conferences and programs aimed at treating the criminal and combating crime before the criminal entered and while he was in prison, but the matter continues to haunt researchers because of the statistics that confirm the existence of this dangerous phenomenon and its increase. To limit the growth of cases of recidivism, one should examine the real causes associated with the crime and focus on the mechanisms of dealing with it and the approaches to address it. This study has come to shed light on the approach of Islamic law in dealing with this phenomenon with a comparison with that of civil law.